2011
DOI: 10.1242/jcs.072918
|View full text |Cite
|
Sign up to set email alerts
|

A novel Chk1/2–Lats2–14-3-3 signaling pathway regulates P-body formation in response to UV damage

Abstract: SummaryProper response to DNA damage is essential for maintaining the integrity of the genome. Here we show that in response to ultraviolet (UV) radiation, the Lats2 tumor suppressor protein is phosphorylated predominantly by Chk1 and weakly by Chk2 at S408 in vivo, and that this process occurs at all stages of the cell cycle and leads to phosphorylation of 14-3-3 on S59 by Lats2. Interaction of Lats2 and 14-3-3 in vivo was confirmed by immunoprecipitation and western blot analysis. Phosphorylated 14-3-3 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 32 publications
(31 citation statements)
references
References 42 publications
1
30
0
Order By: Relevance
“…Importantly, the 14-3-3 family participates in the formation/maintenance of processing bodies (Okada et al, 2011) and stress granules (Stoecklin et al, 2004). These observations, together with our present results, suggest that 14-3-3 may have functional interplay with heat shock proteins, either cooperatively or separately, during formation of these cell structures.…”
Section: Discussionsupporting
confidence: 75%
“…Importantly, the 14-3-3 family participates in the formation/maintenance of processing bodies (Okada et al, 2011) and stress granules (Stoecklin et al, 2004). These observations, together with our present results, suggest that 14-3-3 may have functional interplay with heat shock proteins, either cooperatively or separately, during formation of these cell structures.…”
Section: Discussionsupporting
confidence: 75%
“…The putative roles of these proteins in regulating P-body dynamics are also supported by several recent studies showing that binding of 14-3-3 proteins to EDC3, a P-body component, altered P-body morphology, inhibited miRNA-mediated gene silencing, and changed EDC3's PPIs (Larance et al 2010). Furthermore, phosphorylated 14-3-3g protein (YWHAG) translocates to P-bodies, and knocking down 14-3-3g protein blocks P-body formation after UV damage (Okada et al 2011). It is known that 14-3-3 proteins bind to protein ligands with phosphorylated serine or threonine residues, which, in turn, physically prevent molecular interactions or modulate the accessibility of a target protein to modifying enzymes such as kinases, phosphatases, and proteases (Mhawech 2005;Johnson et al 2010).…”
Section: Discussionmentioning
confidence: 67%
“…We, and others, showed that the Nterminal regions are phosphorylated by several kinases, including Cdc2/cyclin B (S613 of Lats1), NUAK1 (S464 of Lats1), PKCd (S464 of Lats1), Aurora-A (S83 and S380 of Lats2) and Chk1/2 (S408 of Lats2), whereas the C-terminus is phosphorylated by Mst1/2 (S909 and T1079 of Lats1; S872 and T1041 of Lats2). These findings indicate that the N-terminal regions of Lats1/2 contribute to the physiological regulation of these proteins, including subcellular localization, protein stability, or enzymatic activity (Morisaki et al, 2002;Chan et al, 2005;Takahashi et al, 2006;Humbert et al, 2010;Okada et al, 2011;Yabuta et al, 2011).…”
Section: Introductionmentioning
confidence: 83%